2012
DOI: 10.1002/bip.22056
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of poly(propylene imine) dendrimers

Abstract: Dendrimers are highly branched macromolecules with the potential in biomedical applications. Due to positively charged surfaces, several dendrimers reveal toxicity. Coating peripheral cationic groups with carbohydrate residues can reduce it. In this study, the cytotoxicity and genotoxicity of three types of 4th generation poly(propylene imine) dendrimers were investigated. Peripheral blood mononuclear cells (PBMCs) were treated with uncoated (PPI-g4) dendrimers, and dendrimers in which approximately 40% or 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…PPI‐g4 and PPI‐g4‐OS can interact with negatively charged cell membranes owing to their positively charged surfaces and this interaction may block the access of the mitogen to receptors on the cell surface. It is also possible that the lack of proliferation is a consequence of dendrimer genotoxicity 53–56. Because they are able to interact with nucleic acids,7 dendrimers bind to DNA or RNA after entering the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…PPI‐g4 and PPI‐g4‐OS can interact with negatively charged cell membranes owing to their positively charged surfaces and this interaction may block the access of the mitogen to receptors on the cell surface. It is also possible that the lack of proliferation is a consequence of dendrimer genotoxicity 53–56. Because they are able to interact with nucleic acids,7 dendrimers bind to DNA or RNA after entering the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cationic phosphoruscontaining dendrimers induced DNA damage in human mononuclear blood cells, A549 human cancer cells, and human gingival fibroblasts [56]. Similar findings were published for poly(propylene imine) dendrimers and again a clear correlation between surface charge and interactions with the DNA was drawn [57]. Dendrimers mainly interact with nucleic acids on the basis of ionic interactions between the negatively charged backbone phosphate groups and positively charged amino groups of the polymer.…”
Section: Genotoxicitymentioning
confidence: 70%
“…We assume that the higher activity of the PPI‐G4‐OS‐M3 dendrimer result from its structure—the presence of free surface amino groups and positive charge allow for stronger bonding to negatively charged cellular structures. [16a,18] It can be seen in the speed of action (the cytotoxic effect visible after 4 h incubation; Table ) and the number of genes that have been influenced by the dendrimer in question. Results of the independent Ann/PI assay with M3 used at concentrations of 4 and 10 mg mL −1 indicated that the sugar itself does not show any toxicity to MEC‐1 cells (Table S1 and Figure S1, Supporting Information), thus we assume, that it has no influence on gene expression.…”
Section: Resultsmentioning
confidence: 99%